PEMBERANTASAN PENYAKIT PARASITER BERBASIS PEMERIKSAAN KOPROSKOPIS PADA KELOMPOK TERNAK SAPI KERTA NANDINI DESA PETANG - I M, DWINATA; OKA, I B M; DAMRIYASA, I M. (Buletin Udayana Mengabdi; Vol 9 No 1 (2010): Volume 9 No.1 – April 2010, 2012)
ABSTRACT The prevalence of parasite infections of Bali cattle is high, and Bali cattle in Bali is one of the important livestocks. In order to improve the productivity of Bali cattle, control of parasitic diseases is important, especially for pigs raised traditionally in smallholder farmers in Bali. For affectivity of Parasite control in livestock, it should be based on laboratory evidence using coproscopical examination. The public service was conducted in Kelompok Ternak Kertanandini in Petang village of Badung regency. The objective of the activity was to control the parasite infections in Bali cattle based on coproscopical examination. Bali cattle were treated with commercial broad-spectrum antiparasitc drug. . Faecal samples were also collected and examined to identify the gastrointestinal parasite infections in cattle before the treatment. The activity contributes the social and economic wellbeing of smallholder households in this village.